آليات الحد من حوادث المرور حسب القانون 17-05 - زعيتر عاصم (جامعة محمد بوضياف المسيلة, 2018)
إن عدم احترام معظم السائقين لقانون المرور وكثرة حوادث الطرقات التي تؤدي إلى خسائر بشرية ومادية لا تعوض. ومن أجل ردع السائقين والتقليل من الحوادث المعروفة باسم إرهاب الطرقات وأمن هذه الأخيرة وسلامتها. وضع المشرع عدة آليات من بينها الغرامة الجزافية ونظام الرخصة بالنقاط، وكذا إعادة تكوين السائق، حيث أنشأ بطاقية وطنية لرخصة السياقة بالنقاط توضع تحت تصرف وزير الداخلية. تكلف هيئة مختصة بتسيير هذه البطاقية حيث تصنف المخالفات حسب القواعد الخاصة بحركة المرور، يتم سحب نقط أو أكثر من رصيد السائق ويتم استرجاع النقاط ضمن شروط وحالات حددها القانون 17-05 المؤرخ في 17 فبراير 2017، وعند سحب كل النقاط تسحب الرخصة نهائيا ويحال السائق على التكوين من جديد وعلى حسابه. The non- respect of the traffic law by the majority of drivers that’s lead to road accidents which cost to human lives and materials. In order to deter drivers and reduce incidents known as road terrorism and security and safety of the roads. The legislator has set up several mechanisms, including the fines and points system, as well as the driver's re-establishment, where he established a national license card for the points to be placed at the disposal of the Minister of the Interior. The Authority shall be responsible for the operation of this card, where the violations shall be classified according to the traffic rules. One or more points shall be withdrawn from the driver's balance. Points shall be returned within the conditions specified by Law 17-05 of 17 February 2017. Upon the withdrawal of all points, the license shall be withdrawn permanently. The driver is referred to the training again and at his expense.
Keywords: حوادث المرور . الردع . العقوبة . تكوين السائقيين . رخصة السياقة . المراقبة التقنية للسيارات . المخالفات المرورية